Slovak Republic : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
In this paper, the following statistical data are presented in detail: GDP at current and constant prices, GDP by sectors at current and constant prices, employment by sector, average monthly wages, unemployment and vacancies, profit and losses of enterprises, number of enterprises, GDP deflator, consumer price index, producer energy prices, central government assets and financial liabilities, monetary survey and base, interest rates, balance of payments, foreign trade, commodity composition of trade, fiscal operations of state budget, fund and social security funds.